The state-of-the-art survey on integrations and applications of the best worst method in decision making: Why, what, what for and what's next?. (September 2019) - Mi, Xiaomei; Tang, Ming; Liao, Huchang; Shen, Wenjing; Lev, Benjamin
Highlights: A survey of the BWM based on the publications from 2015 to January 2019 is provided. This paper intends to answer five questions about the BWM. This paper has guiding significance for the later research related to the BWM. Abstract: After the first paper regarding the Best Worst Method (BWM) was published in Omega in 2015 ( J. Rezaei, Best-worst multi-criteria decision-making method, Omega 53 (2015) 49–57 ), it has attracted many scholars' attention due to the efficiency of this method in reducing the times of pairwise comparisons and the good performance in maintaining consistency between judgments. Lots of researches related to this method have been published over the past several years. This paper concentrates on the state-of-the-art survey of the BWM based on the in-depth analysis over the publications concerning this method published from 2015 to 26th, January 2019. This paper intends to answer five questions about the BWM: (1) How does this method perform in bibliometric analysis? (2) Why to propose this method and what is it? (3) Which integrations that the BWM were focused on and which areas did they apply to? (4) What extensions of this method were investigated? (5) What are the challenges and future research directions regarding this method? In view of the fact that the research on this method is still in infancy, this paper has guiding significance for the later research related to the BWM. From the theoretical point of view, the reasonable value of consistency ratio, the inconsistency improving methods, the uncertain extensions of the BWM and the techniques for solving multi-optimality model in the BWM are good research issues that need to be further investigated in the future. From the perspective of application, the software packages for this method, the various integrations of this method, the wider application areas, and the international cooperation on this method are good topics to consider.